Effects of glyphosate and its commercial formulation, Roundup® Ultramax, on liver histology of tadpoles of the neotropical frog, Leptodactylus latrans (amphibia: Anura). (July 2018) - Bach, Nadia C.; Marino, Damián J.G.; Natale, Guillermo S.; Somoza, Gustavo M.
Abstract: In the last years, the agricultural expansion has led to an increased use of pesticides, with glyphosate as the most widely used worldwide. This is also the situation in Argentina, where glyphosate formulations are the most commercialized herbicides. It is known that glyphosate formulations are much more toxic than the active ingredient, and this difference in toxicity can be attributed to the adjuvants present in the formula. In this context, the aim of the present study was to evaluate and compare sub-lethal histological effects of the glyphosate formulation Roundup Ultramax and glyphosate active ingredient on Leptodactylus latrans tadpoles at Gosner-stage 36. Semi-static bioassays were performed using 96 h of exposure with Roundup Ultramax formulation (RU; 0.37–5.25 mg a.e./L), glyphosate (GLY; 3–300 mg/L), and a control group. RU exposure showed an increment in the melanomacrophagic cells (MMc) and melanomacrophagic centers (MMCs) from 0.37 mg a.e./L. GLY exposure showed a significant increment in the number of MMc from 15 mg/L, and of MMCs from 3 mg/L. Also, histopathological lesions were observed in the liver of tadpoles exposed to both, GLY and RU. These lesions included: lipidosis and hepatic congestion, but only RU showed significant differences respect to control, with a LOEC value of 2.22 mg a.e./L for both effects. In sum, this study represents the first evidence of adverse effects of glyphosate and RU formulation on the liver of anuran larvae at concentrations frequently found in the environment. Highlights: Glyphosate increased the number of liver MMc and MMCs in L. latrans tadpoles. Liver damages were present on L. latrans larvae exposed to pure and formulated. This is the first report of adverse effects of glyphosate on anuran larvae liver.